PENGEMBANGAN UMKM PRODUK EKSPOR ROOM DIVIDER DARI ASPEK PRODUKTIVITAS PRODUKSI - I Putu Mega Juli Semara Putra; I Dewa Made Endiana; Ni Luh Putu Natha Primadewi; Ni Kadek Dwi Rusjayanthi (KRISNA: Kumpulan Riset Akuntansi, 2018)
Abstract Science Program for Export Products is done at Diva Lamp located in Banjar Sapat Village Tegalalang Gianyar and OMG Lamp in Banjar Gentong Desa Tegalalang Gianyar Regency. Handicraft products produced in the form of room divider that is various kinds of room and interior partitions made of natural materials. The targeted output outcomes include separation of production space planning and product storefront space because in the production room, the laying of facilities such as machinery and work equipment is more permanent, while the product is more neatly arranged so as to create a representative atmosphere for customers. A good layout will provide larger outputs with the same or fewer costs, smaller man hours, and / or reduced working hours. Output is no less important is the procurement of acrylic printing machine. Procurement is expected to reduce the price of production and the length of time the completion of the product so that the resulting product can compete in the market. Improvements in management, bookkeeping, and marketing are done with the aim that administratively UMKM operational can be better organized so that it is easier in planning process, supervision and decision making. In terms of marketing is expected to add a marketing model so that market share can be absorbed more leverage. Keywords: room divider, room partition